2020
DOI: 10.1111/jvim.15952
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and measurement of diuretic responsiveness after oral administration of furosemide to healthy dogs and dogs with congestive heart failure

Abstract: Background: In human patients, cumulative urine volume (uVol) and urine sodium (uNa) can be predicted using spot urine samples and these quantitative measures help detect low diuretic responsiveness (LDR). Hypothesis/objectives: Formulas using spot urine samples predict cumulative uVol and uNa output after oral administration of furosemide to dogs. Animals: Eight healthy dogs, 6 dogs with congestive heart failure (CHF). Methods: Prospective interventional study. Spot urine samples at 180 and 270 minutes after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In the healthy dog, IV furosemide infusion results in urine volume and uNa that are closely correlated, 40 but in dogs with CHF, diuresis and natriuresis, although related, are not interchangeable metrics of responsiveness. 43 Previous studies in humans and dogs measured uNa at specific time points after furosemide dosing and lend support to the concept of uNa-based measures. 8,43,[50][51][52][53] One study in dogs with compensated CHF showed that uNa measured 3 hours after PO administration of furosemide (3 mg/kg) was significantly and highly correlated to the total amount of urinary Na excreted in response to this dose.…”
Section: Urinary Sodium As a Measure Of Diuretic Responsivenessmentioning
confidence: 75%
See 3 more Smart Citations
“…In the healthy dog, IV furosemide infusion results in urine volume and uNa that are closely correlated, 40 but in dogs with CHF, diuresis and natriuresis, although related, are not interchangeable metrics of responsiveness. 43 Previous studies in humans and dogs measured uNa at specific time points after furosemide dosing and lend support to the concept of uNa-based measures. 8,43,[50][51][52][53] One study in dogs with compensated CHF showed that uNa measured 3 hours after PO administration of furosemide (3 mg/kg) was significantly and highly correlated to the total amount of urinary Na excreted in response to this dose.…”
Section: Urinary Sodium As a Measure Of Diuretic Responsivenessmentioning
confidence: 75%
“…Previous studies in humans and dogs measured uNa at specific time points after furosemide dosing and lend support to the concept of uNa‐based measures 8,43,50‐53 . One study in dogs with compensated CHF showed that uNa measured 3 hours after PO administration of furosemide (3 mg/kg) was significantly and highly correlated to the total amount of urinary Na excreted in response to this dose 43 .…”
Section: Urinary Sodium As a Measure Of Diuretic Responsivenessmentioning
confidence: 82%
See 2 more Smart Citations
“…In these papers, the diuretic has been administered over a dose range of 0.13 mg/kg/day to 0.5 mg/kg/day, and spironolactone (an aldosterone receptor antagonist) has been administered at dosages from 0.49 mg/kg once daily to 2 mg/kg once daily. These drugs are very useful in the therapy of CHF secondary to MMVD in dogs [ 362 , 363 , 364 , 365 , 366 , 367 , 368 , 369 ].…”
Section: Resultsmentioning
confidence: 99%